2015
DOI: 10.1021/ic5031125
|View full text |Cite
|
Sign up to set email alerts
|

C–F Bond Activation by Transient Phosphenium Dications

Abstract: C-F bond cleavage by transient phosphorus(III)-based dications [RP(C(PPh3)2)](2+) (4a(2+), R = Ph; 4b(2+), R = 4-F-Ph) is reported. These dications were generated by reaction of the corresponding monocationic precursors with excess Na[BAr4(Cl)]. Evidence for the existence of transient dicationic species was obtained by trapping the dication 4a(2+) with PMe3. According to theoretical analysis, the low-lying lowest unoccupied molecular orbitals of these species were responsible for the observed activation of C-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Vidović reported the synthesis and characterization of the chlorinated cations [( 130 )­P III (Cl)­Ph] + ( 554a ) and [( 130 )­P III (Cl)­(4–F-C 6 H 4 )] + ( 555b ) from 130 and the appropriate Cl 2 PAr in excess (Scheme ). In addition to the indicative NMR pattern, the atom connectivity of [ 555b ]­[Cl] was established by XRD analysis. Heating of [ 554a ]­[Cl] at 100 °C overnight in presence of [Na]­[BAr F 4 ] (3 equiv) produced the fluorinated cation 557a in minimal amounts that precluded its isolation.…”
Section: Geminal Dianions Of Type III (A and B: Cationic Fragments)mentioning
confidence: 99%
“…Vidović reported the synthesis and characterization of the chlorinated cations [( 130 )­P III (Cl)­Ph] + ( 554a ) and [( 130 )­P III (Cl)­(4–F-C 6 H 4 )] + ( 555b ) from 130 and the appropriate Cl 2 PAr in excess (Scheme ). In addition to the indicative NMR pattern, the atom connectivity of [ 555b ]­[Cl] was established by XRD analysis. Heating of [ 554a ]­[Cl] at 100 °C overnight in presence of [Na]­[BAr F 4 ] (3 equiv) produced the fluorinated cation 557a in minimal amounts that precluded its isolation.…”
Section: Geminal Dianions Of Type III (A and B: Cationic Fragments)mentioning
confidence: 99%
“…In a related sense, Gudat has pioneered the reactivity of the masked phosphenium cations derived from N‐heterocyclic phosphines . Recently the Vidović group showed that P III dications exhibit stoichiometric activation of C−F bonds at 100 °C, albeit with a limited scope of substrates (only α‐phenyl C−F bonds) . The same group also showed abstraction of hydrides from silanes and amine/pyridyl‐boranes under ambient conditions .…”
Section: Figurementioning
confidence: 99%
“…Although previously unknown, Vidovic and co‐workers reported the first example of C−F bond activation by a Lewis acidic P III species in 2015. These authors described the formation of the transient phosphenium dications, [PhP(C(PPh 3 ) 2 )] 2+ , generated by chloride abstraction from the corresponding monocation [PhPCl(C(PPh 3 ) 2 )] 4 . The dication was intercepted with the addition of PMe 3 as [PhP(PMe 3 )(C(PPh 3 ) 2 )] 2+ 5 (Scheme ), but the chemistry showed an interesting anion dependence.…”
Section: Phosphorus(iii) Cationic Lewis Acidsmentioning
confidence: 99%